Acute and subacute effects of oropharyngeal sensory stimulation with TRPV1 agonists in older patients with oropharyngeal dysphagia: a biomechanical and neurophysiological randomized pilot study. (April 2019) - Tomsen, Noemí; Ortega, Omar; Rofes, Laia; Arreola, Viridiana; Martin, Alberto; Mundet, Lluís; Clavé, Pere
Background: Older people with oropharyngeal dysphagia (OD) present a decline in pharyngeal sensory function. The aim of this proof-of-concept study was to assess the biomechanical and neurophysiological effects of acute and subacute oropharyngeal sensory stimulation with transient receptor potential vanilloid 1 (TRPV1) agonists (capsaicinoids) in older patients with OD. Methods: We studied the effect of a single dose versus multiple doses (2 weeks) of oral capsaicin treatment (10 –5 M) or placebo in 28 older patients with OD (81.2 ± 4.6 years) using videofluoroscopy (penetration-aspiration scale [PAS], timing of swallow response) and electroencephalography (EEG) (latency and amplitude of pharyngeal event-related potential [ERP]). Results: Acute stimulation by capsaicinoids 10 –5 M did not improve swallow function and did not produce significant changes in pharyngeal ERP. In contrast, after 10 days of treatment, patients presented a clinically relevant and statistically significant reduction in the laryngeal vestibule closure (LVC) time (22.5%, p = 0.042), and in the PAS (24.2%, p = 0.038), compared with the placebo group. EEG results showed a reduction in the latency of the N1 peak (28.6%, p = 0.007) and an increase of the amplitude of the P1-N2 (59.4%, p = 0.038) and the N2-P2 (43.6%, p = 0.050) peaks. We observed a strong and significant correlation between the reduction in the latency of the N1 peak and change in LVC time after subacute treatment ( r = 0.750, p = 0.003). Conclusions: After 2 weeks of treatment, oropharyngeal sensory stimulation with capsaicinoids induced cortical changes that were correlated with improvements in swallowing biomechanics in older patients with OD. These results further show that sensory stimulation by TRPV1 agonists can become a useful pharmacological treatment for older patients with OD.